PENCEGAHAN PENYAKIT AKIBAT JAJANAN SEKOLAH DENGAN EDUKASI KESEHATAN DAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Naully, Patricia Gita; Mathilda, Fiorida (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Foodborne disease is an illness caused by food or drink which had been contaminated with pathogenic microbes. This case occurs oftentimes in schools and can affect health, learning outcomes, achievements, and children?s development. Therefore, the disease which caused by food sold in school should be prevented by health and Consumer Protection Act (UUPK) education activities. Community service activities in the form of counseling about the hazards of microbial contaminated food and UUPK in SD Negeri Sariwangi aims to improve the knowledge of students related to it. This activity was conducted six times in July-September 2017. Participants of this activity are every students of SD Negeri Sariwangi, 360 in total. Extension was done by lecturing and ?question and answer? method. Evaluation results showed an increase in the average score of students on the given test, from 42 to 75. A total of 75.83% claimed to have a high level of understanding of health materials and 61.1% of UUPK material. This extension can increase students' knowledge of foodborne diseases, the characteristics of microbial contaminated foods, the prevention of disease transmission through snack, and their rights and obligations as consumers are written in the Law of Republic Indonesia Number 8 Year 1999 on Consumer Protection.